Physical modeling and the fracture toughness of sea ice 1986 - Parsons, B. L.; Snellen, J. B.; Hill, B. (National Research Council of Canada. Institute for Marine Dynamics, 1986)
The fracture toughness of sea ice was obtained in situ in order to better model ice mechanical properties in the IMD ice tank. The anisotropy of sea ice is reflected in the dependence of fracture toughness, with a different temperature dependence. NRC publication: Yes